Tingkat Kelayakan Media Video Pembelajaran Pada Kompetensi Dasar Membuat Desain Busana Rumah Sesuai Konsep Kolase Di Smk Cendika Bangsa Malang - Mustika Rahmawati; Deny Arifiana (Journal on Education, 2023)
Video is a type of media that can visualize images with sound that connected with each other including 4 elements (text, pictures, sound and animation) that make students tend to pay attention and can increase their curiosity about learning materials. The aims of this study to describe the eligibility of video as a learning media for basic competence create home fashion designs according the collage concept. This research use type of Research and Development (RnD) with ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The type of data used in this research is quantitative descriptive data. The research instrument is form of questionnaire given to the validator to determine the aligibity of video in terms of material and media aspects. Data collection techniques used are questionnaires. The result showed The eligibility level of learning video from material aspect got an average result of 3.6 included in the very eligibility criteria, and from media aspect got an average of 3.7 included in the very eligibility criteria. It can be concluded that learning video media is appropriate to be applied to fashion design learning for basic competence create home fashion designs according the collage concept.